Reforming fertilizer import policies for sustainable intensification of agricultural systems in Sri Lanka: Is there a failure? - Weerahewa, Jeevika; Senaratne, Athula; Babu, Suresh Chandra (Michigan State University, 2021)
The government of Sri Lanka has implemented a myriad of fertilizer import and use options during 2015 – 2021 with the objective of making agricultural systems more financially and environmentally sustainable. However, these actions were not fully informed by global and national evidence. This brief illustrates how the fertilizer environment influences the performance of agricultural systems in Sri Lanka, reviews past changes and presents a set of options for sustainable intensification of Sri Lankan agricultural systems.